Biomimetic Elastin-Like Polypeptides as Materials for the Activation of Mechanophoric Catalysts - Funtan, Sebastian; Funtan, Anne; Paschke, Reinhard; Binder, Wolfgang H. (Organic Materials, 2020)
Elastin-like polypeptides (ELPs) are well known for their elastic and thermoresponsive behaviors. Their elasticity originates from the formation of a β-spiral which is the consequence of stacking type-II β-turns, formed from individual VPGVG pentapeptide units. Here, the synthesis of ELPs of varying chain lengths [VPGVG, (VPGVG)2, and (VPGVG)4] and their coupling to a mechanoresponsive catalyst are reported. The attached ELP chains can act as “molecular springs,” allowing for an efficient uptake and transmission of an applied force to the mechanophoric bond. This leads to stress-induced activation of the mechanophoric catalyst, in turn transforming mechanical energy into a “click” reaction. Secondary structure analysis via IR and CD spectroscopy revealed that the β–spiral formation of the ELP is not affected by the coupling process and the β–spiral is still intact in the mechanocatalyst after the coupling. Mechanochemical activation of the synthesized catalysts by an external applied force, studied via ultrasonication, showed conversions of the copper(I)-catalyzed alkyne-azide “click” reaction (CuAAC) up to 5.6% with an increasing chain length of the peptide, proving the potential to incorporate this chemistry into biomaterial engineering.
Keywords: Elastin-like polypeptides; β-spiral; peptide coupling; copper(I); “click” reaction; mechanochemistry; mechanocatalysts